Teaching as performing art - Hajmássy Hella (2005)
This thesis examines what advantages could be taken from the idea of teaching and acting being similar. Basic subjects which are taught in actor training might be considered to be adapted and used in teacher training as well, in order to empower teacher trainees with additional skills. With the help of these skills, students' attention can be held along the lesson and the teaching process might become more effective. Using rhetorical, psychological, methodological proofs as well as drama bibliography along with examples I will attempt to demonstrate why it would be crucial to apply essential acting techniques in teaching.